‘Truth and Reconciliation’: A Critical Step Toward Eliminating Race and Gender Violations in Tenure Wars - Kupenda, Angela mae; Lawson, Tamara F. (Columbia Journal of Gender and Law, 2015)
Women and other underrepresented groups have fought valiantly to render legal education inclusive regardless of one’s race or gender. Clashing with a status quo denying access to individuals in underrepresented groups, they battled first just to gain admission to law schools as students and then to be admitted to the Bar. The struggle continued as they also sought to be hired on the permanent faculty at various institutions.